The psychological impact of partner abuse on women and their relationships : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in Psychology - Verzyde, Kimberlee H (Massey University, 1996)
Psychosocial and relationship factors were investigated in relation to partner abuse in a survey of 104 New Zealand female tertiary student volunteers. Using the Conflict Tactics Scales partner abuse was categorised in four ways: verbal and physical abuse occurring within the year preceding the study, and verbal and physical abuse occurring prior to that. Compared to non-abused students, students who had been verbally abused during the year preceding the study used exit more as a problem-solving style, and rated themselves less effective in problem-solving, less committed to the relationship, less satisfied with the relationship, more attracted by alternatives to the relationship and more inclined to have an external locus of control for relationship satisfaction. Students who were verbally abused during the year preceding the study were also subject to more general feelings of distress and to negative affect, while rating their partners less effective in problem-solving, and more repressive of their autonomy and relatedness needs. Students who had been verbally abused prior to the year leading up to the study differed from non-abused students in sociability. Students who were physically abused during the year preceding the study differed from non-abused students in their perceptions of the effectiveness of their approach to problem-solving, and in closeness to their partner. Students who had been physically abused prior to the year leading up to the study differed from non-abused students in ratings of their partner's use of hostile control. These results support the findings of studies carried out across clinical samples, and indicate that abused women do differ from non-abused women across a range of psychosocial and relationship factors.
Keywords: Wife abuse; Physical abuse; Verbal abuse; Relationship factors